Carious lesion severity and demarcated hypomineralized lesions of tooth enamel in schoolchildren from Melbourne, Australia. (11th July 2018) - Gambetta‐Tessini, K; Mariño, R; Ghanim, A; Calache, H; Manton, DJ
Abstract: Background: Developmental hypomineralized lesions of enamel (DHL) may represent a significant caries‐risk factor. The aim of this study was to determine the association between carious lesion severity and DHL in 6‐ to 12‐year‐old schoolchildren from Melbourne, Australia. Methods: The sample was derived from randomly selected schools in inner Melbourne. A full dental examination was performed at the school. Socio‐demographic data, caries experience (DMFT/dmft/ICDAS II) and the consequences of untreated carious lesions (PUFA/pufa) were measured. DHL, molar incisor hypomineralization (MIH) and hypomineralized second primary molar (HSPM) presence were assessed using the European Academy of Paediatric Dentistry (EAPD) criteria. Results: Of the children examined (n = 327), 26.9% had DHL. The prevalence of MIH and HSPM was 14.7% and 8%, respectively. Almost 20% of children had severe carious lesions (ICDAS 5 & 6) in at least one permanent or primary tooth. Ordinal regression analyses indicated that DHL (OR = 2.17; 95% CI: 1.35–3.49) and being born overseas (OR = 2.59, 95% CI: 1.66–4.06) increased the likelihood of severe carious lesions. Conclusions: One of four children had DHL. DHL‐affected children had an increased likelihood of presenting untreated severe carious lesions compared with DHL‐free children.